Pengaruh Kesadaran Wajib Pajak, Sanksi Perpajakan dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Ni Kadek Suarniti; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2022)
Taxpayer compliance has always been an important component in increasing tax revenue. This observe aims to decide how much affect Taxpayer consciousness, Tax Sanctions, and best of service have on Motor Vehicle Taxpayer Compliance. The populace in this study have been all taxpayers registered on the SAMSAT Karangasem Workplace, amounting to 897,982 and the sample in this observe turned into a hundred respondents calculated based at the unintentional slovin sampling components. Statistics turned into accumulated through the use of a survey method thru a questionnaire. The records analysis method used in this research is multiple linier regression. Primarily based at the analysis, it shows that taxpayer awareness has a wonderful and sizable impact on Taxpayer compliance, tax sanctions havent any extensive impact on taxpayer compliance, while provider first-class has a wonderful and huge impac